Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1055/s-0032-1327734
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Metformin on Weight Loss in Non-Diabetic Individuals with Obesity

Abstract: Objective: The efficacy of metformin for the treatment of obesity has been evaluated in few clinical trials with inconclusive results. Moreover, the effectiveness in a real-life outpatient setting has not been tested until today. In this study we aimed to examine the effectiveness of metformin as a weight reducing drug in obese and overweight patients with regard to their degree of insulin resistance. Design and patients: We treated 154 consecutive patients with a body mass index ?27?kg/m2 in an outpatient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
2
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(162 citation statements)
references
References 20 publications
(21 reference statements)
6
144
2
10
Order By: Relevance
“…51,55 The remaining 12 studies (2 studies were single-group pre-post designs, 1 study had a more active comparison group, and 9 studies reported outcomes at < 12 mo) were only included in analyses of adverse events. 24,29,57,63,[75][76][77][78][79][80][81]83 High within-group heterogeneity was common; however, the direction of treatment effect was consistent across most studies, and the confidence intervals overlapped. This statistical heterogeneity is likely due to small versus large treatment effects observed across studies.…”
Section: Resultsmentioning
confidence: 99%
“…51,55 The remaining 12 studies (2 studies were single-group pre-post designs, 1 study had a more active comparison group, and 9 studies reported outcomes at < 12 mo) were only included in analyses of adverse events. 24,29,57,63,[75][76][77][78][79][80][81]83 High within-group heterogeneity was common; however, the direction of treatment effect was consistent across most studies, and the confidence intervals overlapped. This statistical heterogeneity is likely due to small versus large treatment effects observed across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among diabetics, metformin alters glucose production and may have an effect on insulin production. It also had an effect in weight loss [18]. In addition to anti-diabetic treatment effect, metformin is shown to relieve the pain and inflammation intensity of OA with no reported side effects that make it as a treatment choice in patients with knee OA and serve as a potential drug for inflammation-related disorders [19].…”
Section: Metforminmentioning
confidence: 99%
“…and nondiabetic adults (UKPDS Group, 1998;Glueck et al, 2001;Kay et al, 2001;Seifarth et al, 2013). In addition, metformin enhances leptin sensitivity in high fat-fed obese rats (Kim et al, 2006) and induces weight loss (metformin at 300 mg/kg caused a ∼6% weight loss relative to vehicle by day 7 of treatment) in diet-induced obese (DIO) mice (Kim et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%